Kosmiese wet, noodsaaklikheid en waarskynlikheid: 'n Christelike perspektief vanuit die Wysbegeerte van die Kosmonomiese Idee (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2024)
In a previous article, an outline was mainly given of Armstrong’s view of natural laws and probability laws and Van Fraassen’s criticism thereof. In this article, an attempt is made to account for the problems dealt with in the previous article from a Christian perspective. The identity problem and the conclusion problem cannot be adequately solved if it is not realized that the individual (entity) also has a universal side, and consequently the distinction between concept and idea also comes into play here. In this article, it is further claimed that the identification and conclusion problem refer respectively to the law side and the factual side of reality. It is also concluded that natural laws are modal laws which are unspecified universal laws and statistical laws are typical laws which are specified universal laws. Although not discussed in detail, the point is highlighted that without, among other things, the quantitative, spatial, kinematic and physical aspects of reality, there is no way to form a comprehensive idea of what natural and probability laws are.